Equilibrium analysis of carbon decision behavior for the evolutionary game between the government and enterprises - Ding, Youqiang; Hu, Yufeng; Liu, Jun (Frontiers in Energy Research, 2022)
With the implementation of the carbon-neutral goal, an evolutionary game of carbon decision behavior was derived from the difference between government carbon mitigation and enterprises’ performance growth. This paper constructed a double-performance objective function of environmental performance and corporate performance (DP). Four carbon decision factors such as carbon emission rights, carbon tax, green innovation, and green subsidy were added separately into the DP model to search for the equilibrium point by Stackelberg Game. The research shows that: (ⅰ)The price effect of carbon emission rights can restrain the excess carbon emission of enterprises to a certain extent; (ⅱ) The reverse effect of a carbon tax can force enterprises to achieve the carbon mitigation goal through green innovation; (ⅲ) The reinforcement effect of green innovation can strengthen the promotion of environmental performance but accelerate the decline of corporate performance; (ⅳ) The incentive effect of green subsidy can make corporate performance reach the inflection point ahead of time and realize DP synergistic growth. The evolutionary game between the government and enterprises results in the fluctuation change that causes DP to rise first and then decrease and finally increase. And DP can be developed in a synergy way under collaborative governance for their consistency of carbon decision behavior.